Generational diversity in the organizational environment: Construction of Knowledge Based on International Literature (Management and Connections Journal, 2024)
This article sought to identify the characteristics of international scientific publications related to the topic of Generational Diversity in the Organizational Environment. For the construction of the Final Bibliographic Portfolio (PBF), the Knowledge Development Process – Constructivist (Proknow-C) was used as an intervention method. The research axes were defined and the articles selected based on research in the Scopus and Web of Science databases. It reached 26 articles with cult, recognition and certification to the research theme. It was evident that the studies analyzed were limited to describing the main characteristics of the generations, with little attention to aspects related to the coexistence of two or more generations in the same workspace.
Keywords: generational diversity in the workplace; generations; proknow-c; bibliometric analysis